WUJUD DAN EMANASI DALAM PANDANGAN IBNU ARABI - Zulkifli Zulkifli Zulkifli (Fakultas Ushuluddin Adab dan Dakwah IAIN Metro-Lampung, 2017)
Al-Farabi decribes the sequences of ovents that may be a form of (natural beings) of substances that must be al-being (God). He asked that God is a mind that is not a thing. Evrything emanates (emanation) of god, becouse god knows (think) his substance and who knew that he was the cause of all his known form. Then the non-physical beings that there is absolute a lot, so that the amount can be rated in a hierarchy, culminating in a god. How does it happen emansi, Farabi explains that God is really the One at all. Becouse he came out of him as well of one form only. When he came out off the form of God who spelled, it means, it‘s god spelled substance.